Pengaruh Sosial Media Instagram Sebagai Sarana Promosi Dalam Meningkatkan Keputusan Pembelian Madu Onggu Di Sidoarjo - Purnamasari, Intan; Kurriwati, Nirma (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to investigate the impact of social media advertising on consumer purchasing decisions for onggu honey products in Sidoarjo. The research employs a quantitative technique in its quantitative descriptive investigation. The analysis used in this study is a simple linear regression analysis. The data collecting method involves distributing questionnaires to honey consumers much as 97 respondents. Studies indicate that using social media for advertising has a positively and significantly influence on the purchasing choice of onggu honey products in Sidoarjo.